What satellites see vs what pastoralists know: A mapping story from the Karamoja Cluster - Basel, Ashleigh; Chepngetich, Brenda; Tsoka, Jonathan; Kenduiywo, Benson; Craparo, Alessandro (2025)
This carousel tells the story of how mapping for climate resilience and peace works best when satellite data is combined with local knowledge. Focusing on the Karamoja Cluster across Uganda, Kenya, South Sudan, and Ethiopia, it shows why understanding mobility, drought, and resource tension requires seeing beyond what remote sensing alone can capture. The carousel walks through a two-phase mapping process: first, large-scale remote mapping using satellite imagery and machine learning, and then participatory mapping with local communities to fill critical gaps. Pastoralists helped identify missing buildings, seasonal resources, and local realities invisible to satellites. The result is a richer, more accurate dataset that reflects how people actually live and move. The key message is that maps shape decisions about aid, services, and investment, and without grounding data in lived experience, even well-designed systems can fail